PROSES PEMBENTUKAN MAKNA ATAS PELECEHAN SEKSUAL VERBAL DALAM INTERAKSI KOMUNIKASI GAMERS PEREMPUAN DI ROBLOX - Geneva Faradilla Hermar; Joyo Nur Suryanto Gono (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Verbal sexual harassment is a common experience among female gamers in Roblox through voice chat and public chat features, creating a gender unequal interaction space. This study aims to understand how female gamers construct meanings of verbal sexual harassment experienced in Roblox. Using an interpretive paradigm, this descriptive qualitative study involved seven female gamers aged 18–22 who had experienced verbal sexual harassment in Roblox. Data were collected through in depth interviews and analyzed using thematic analysis, guided by the Coordinated Management of Meaning (CMM) theory and Ziyu Deng’s concept of reluctance in recognition. The findings reveal that meaning coordination occurs through four stages: responding to harassment, interpreting others’ reactions, discussing the experience, and establishing a final meaning. Different constitutive and regulative rules at various levels of the hierarchy of meaning lead participants to interpret similar situations differently. The resulting meanings include verbal sexual harassment, ragebaiting, joking, trolling, and hate speech, shaped by prior experiences, situational contexts, and dialogue with others.